Group Work Around the Globe: Creating transformative connections in challenging times - Wilkins, Christine; Doel, Mark; Skolnik, Sari; Genke, John; Gardella, Lorrie Greenhouse (Whiting & Birch Ltd, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Introduction to Klaus-Martin Ellerbrock, Theses on Working with Refugees in Germany: Considering the Experiences of Louis Lowy - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Introduction to Olga Derkachova, Children of War: Exploring the Trauma of War through Collective Creative Writing in Literary Workshops - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

“My sister is the one that made me stay above water”: How social supports are maintained and strained when survivors of intimate partner violence reside in emergency shelter programs - Stylianou, Amanda M.; Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Interpersonal Violence, 2018)
While social support is critical in helping intimate partner violence (IPV) survivors heal and build hope, social isolation is a frequent experience for survivors. For survivors residing in domestic violence (DV) emergency shelters, the isolation from social supports is often exacerbated by shelter rules and policies. This study uses a 20th century feminist framework to understand the ways in which social support networks are maintained and/or strained when survivors reside in DV emergency shelters. Among this sample of 76 survivors, 40 participants identified family members as their support system, with siblings and mothers most frequently identified, and 14 participants identified friends as their social support. Prior to entering the DV shelter, survivors reported that their support networks provided encouragement and motivation along with emotional support, financial and material support, and support with children. Participants spoke about the process of informing their support systems of the transition into a DV shelter, the positive and negative impacts of the transition on their support system, and the roles that frequent telephone calls and texts played in maintaining their support networks. Participants reported positive impacts of residing in a DV shelter including improved emotional and physical health, strengthened emotional relationships, and improved physical and emotional resource provision. For those participants reporting negative experiences, they frequently identified logistical barriers, including the inability to receive visitors at the shelter, the distance between them and their friends and family, and strict rules around curfew and child care. Our findings invite researchers and practitioners to consider further examination of best practices around programming that supports survivors in maintaining social supports while residing in shelter programs
Keywords: dept.swk; peer-reviewed

Welcome the stranger: Group work and hospitality in a fearful era - Gardella, Lorrie Greenhouse (Group work around the globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking

Retooling the health care workforce in the era of the Affordable Care Act: An evaluation of an advanced certificate program in integrated primary and behavioral health care - O’Brien, Kyle H.; Acri, Mary C.; Campanelli, Peter C.; Cerniglia, Joseph A.; McKay, Mary M. (Journal of Teaching in Social Work, 2018)
The Affordable Care Act aims to increase affordable coverage, reduce overall costs, and improve health outcomes. To achieve these aims, new knowledge and skills must be built within the existing workforce. The purpose of this article is to examine the behavioral and organizational changes brought about by an educational program that aimed to retool the healthcare workforce for the implementation of integrated primary and behavioral healthcare models, with an added emphasis on prevention. Sixty-three participants of an Advanced Certificate Program completed 1 or more evidence-informed learning modules centered on integrated primary and behavioral health care. The vast majority of students who completed each of the 5 modules of the program reported acquiring new knowledge and skills. Student satisfaction of the program met or exceeded overall expectations. In addition, program participation has resulted in not only students’ intentions to change workplace practices but also actual implementation of workplace changes related to integrated care models. The Advanced Certificate Program appears to be a promising platform for service providers to align their knowledge and skills with the premises of current healthcare reform. © 2018, © 2018 Taylor & Francis.
Keywords: Affordable Care Act; Integrated primary and behavioral health care; certificate programs; dept.rec; dept.swk; integrated care; peer-reviewed; workforce training

An Examination of the Relationship between Maternal Depression and Barriers to Child Mental Health Services - Acri, Mary C.; Bornheimer, Lindsay; Hamovitch, Emily; Lambert, Kate (Children and Youth Services Review, 2018)
Objective: Maternal depression is a common, chronic set of disorders associated with significant burden to caregivers, children and families. Some evidence suggests that depression is associated with perceptions of barriers to child mental health treatment and premature termination from services. However, this relationship has not yet been examined among a predominantly low-income sample, which is at disproportionately high risk of depression, child mental health problems, and treatment drop out. Accordingly, the purpose of this study is to examine the relationships between caregiver depression and perceived barriers to treatment. Methods: Three hundred twenty (n=320) children between the ages of 7 to 11 and their caregivers were assigned to either the 4 Rs and 2Ss for Strengthening Families, which is a multiple family group intervention, or services as usual (SAU) consisting of typical outpatient mental health services. Caregiver depression was measured by the Center for Epidemiologic Depression Scale; perceived barriers to treatment were assessed via the Kazdin Barriers to Treatment Scale. Results: Clinically significant levels of depressive symptoms at baseline were significantly associated with greater scores in all four barriers to treatment subscales (stressors and obstacles competing with treatment, treatment demands and issues, perceived relevance, relationship with therapist) at post-test. Conclusions: Addressing maternal mental health, and attending to stressors that impede poverty-impacted families from child services is critical for the health and functioning of caregivers, and to ensure that children with mental health problems receive treatment.
Keywords: dept.swk; peer-reviewed

Mining for Posttraumatic Growth (PTG) in Sexual Minority Women Who Survive Intimate Partner Violence: A Conceptual Perspective. - Counselman-Carpenter, Elisabeth; Redcay, Alex (Behavioral Sciences, 2018)
This theoretical paper explores the need to use posttraumatic growth (PTG) as a framework when studying sexual minority women (SMW) who are survivors of intimate partner violence (IPV) to examine the relationship between risk factors such as stress, anxiety and alcohol use and to understand the role of protective factors through mining for the presence of posttraumatic growth (PTG). Despite a call for continued research in this highly vulnerable population, representative studies of SMW and PTG remain extremely limited. Research that examines the relationship between IPV, behavioral health issues, and posttraumatic growth would provide the opportunity to develop tailored intervention models and opportunities for program development to decrease isolation and increase factors of posttraumatic growth. In particular, the impact of how interpersonal relationships as potential mediators and/or outcomes of posttraumatic growth (PTG) needs to be explored more thoroughly. PTG is a valuable framework for vulnerable populations such as sexual minority women because it focuses on how transformative change may result from traumatic experiences such as surviving IPV.
Keywords: Intimate partner violence; Post-traumatic growth; Sexual minority women; dept.swk; intimate partner violence; peer-reviewed; sexual minority women

Barriers and facilitators to mental health screening efforts for families in pediatric primary care - Acri, Mary; Zhang, Shirley; Chomanczuk, Aminda H.; O’Brien, Kyle H; De Zitella, Maria L. Mini; Scrofani, Paige R.; Velez, Laura; Garay, Elene; Sezer, Sara; Little, Virna; Cleek, Andrew; McKay, Mary M (Journal of Family Social Work, 2018)
The purpose of this commentary was to describe the barriers and facilitators to mental health screening efforts for children between age 5 and 18 years within three primary care clinics in poverty-impacted communities as part of an integrated care model. Three screeners, two women and one male, participated in a screening effort between September and December 2015. Screeners were interviewed about their perceptions of barriers and facilitators to screening. Organizational, family, and screener-level factors were found to influence delivery of screenings to children. Given the benefits of screening in primary care settings, identifying barriers to these initiatives and ways to address them pre-emptively could potentially alter the developmental trajectory and outcomes of children at risk for serious mental health conditions. © 2018, © 2018 Taylor & Francis.
Keywords: Screening and detection efforts; article; case report; child; child mental health; clinical article; dept.rec; dept.swk; female; human; human experiment; integrated care; male; mental health; outcome assessment; peer-reviewed; perception; poverty; primary medical care

From Values to Passion to Enlivened Practice: A Palette of Possibilities - Keenan, Elizabeth (Reflections: Narratives of Professional Helping, 2018)
This narrative offers a palette of possibilities for linking micro and macro practices that arose from interviews with social workers who were viewed as addressing the profession’s dual purpose of individual well-being and social justice in their practice. I begin with my own experiences and desires to link micro and macro together as a clinical social worker and community organizer. An interlude describing the way the social workers stretched my thinking comes in between the themes. I conclude with a final reflection on the impact of their stories and implications for future research and practice.
Keywords: Macro Practice; Micro Practice; Social Justice; Well-Being; dept.swk; macro practice; peer-reviewed; social justice; social work methods; social work practice; values; ⛔ No DOI found

Multiple family group service delivery model for children with disruptive behavior disorders: Impact on caregiver stress and depressive symptoms - Gopalan, Geetha; Bornheimer, Lindsay A.; Acri, Mary; Winters, Andrew; O’Brien, Kyle H.; Chacko, Anil (Journal of Emotional and Behavioral Disorders, 2018)
Disproportionately high rates of caregiver stress and depression are found among poverty-impacted communities, with high levels of caregiver stress and depression putting youth at heightened risk for the onset and perpetuation of disruptive behavior disorders. The purpose of this study was to examine the effects of a behavioral parent training program called the 4Rs and 2Ss for Strengthening Families Program (4R2S) on caregiver stress and depressive symptoms among 320 youth aged 7 to 11 and their families assigned to either the 4R2S or services as usual (SAU) condition. Among caregivers with clinically significant (CS) scores at baseline, 4R2S participants manifested significantly reduced scores on the stress and depressive symptom scores to SAU participants at 6-month follow-up. Findings suggest that 4R2S may reduce caregiver stress and depressive symptoms among those caregivers initially manifesting CS levels of stress or depressive symptoms.
Keywords: dept.rec; dept.swk; peer-reviewed

Stigma, housing and identity after prison. - Keene, Danya E; Smoyer, Amy B; Blankenship, Kim M (The Sociological review, 2018)
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.
Keywords: Housing; Incarceration; Spatial stigma; dept.swk; peer-reviewed

Social work and hospitality: An oral history of Edith Stolzenberg - Gardella, Lorrie Greenhouse (Journal of Religion & Spirituality in Social Work: Social Thought, 2018)
Edith Richman Stolzenberg (1913–2004) was the first woman to be hired as a social worker in Hartford Public High School in Hartford, Connecticut. In a career that spanned 60 years and much of 20th-century social welfare history, she was motivated by the social justice tradition of her Jewish upbringing and the religious value of hospitality to advocate for children and families. As we enter a harsh new era for social services, this oral history explores the radical possibilities for integrating social work goals and religious values.
Keywords: adolescents; children; community; dept.swk; ethics; hospitality; oral history; religion; social work practice

An Examination of Peer-Delivered Parenting Skills Programs Across New York State - Acri, Mary C.; Craig, Nancy; Adler, Josh (Community Mental Health Journal, 2018)
Peers are an important adjunct to the public mental health service system, and are being increasingly utilized across the country as a cost-effective solution to workforce shortages. Despite the tremendous growth of peer-delivered support over the past two decades, it has only been within the past few years that peer programs have been the subject of empirical inquiry. The purpose of this study was to examine the prevalence and characteristics of peer-delivered parenting programs across the New York State public mental health service system. We surveyed 46 family peer organizations across New York State regarding their delivery of structured peer-delivered parenting programs. Thirty-four (76%) completed the questionnaire, and of them, 18 (53%) delivered a parenting program. Subsequent interviews with seven of the 18 organizations revealed peer organizations had been delivering eight unique parenting programs for upwards of two decades. Additionally, organizations offered multiple supports to families to participate. Training, supervision, and issues around fidelity are discussed, as well as the implications of this study for states utilizing a peer workforce.
Keywords: Adolescent; Behavior parent training programs; Child; Child, Preschool; Education, Nonprofessional; Humans; Infant; Infant, Newborn; Mental Health Services; New York; Parents; Peer Group; Peer support services; Peer-delivered family support; Surveys and Questionnaires; dept.swk; peer-reviewed